2008
DOI: 10.1016/j.cbi.2008.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of an invertebrate acetylcholinesterase by sulfhydryl reagents: A reconsideration of the implications for insecticide design

Abstract: Previously we used site-directed mutagenesis, in vitro expression, and molecular modeling to investigate the inactivation of an invertebrate acetylcholinesterase, cholinesterase 2 from amphioxus, by the sulfhydryl reagents 5,5'-dithiobis(2-nitrobenzoic acid) (DTNB) and N-ethylmaleimide (NEM). We created the mutants C310A, C466A, C310A/C466A and C310A/F312I to assess the roles of the two cysteines and a proposal that the increased rate of inactivation previously found in an F312I mutant was due to increased acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, it has been reported that iodoacetamide-containing AChE inhibitors do not bond covalently to Ag AP-AChE [17] . Since iodoacetamide is a commonly used sulfhydryl agent, such a finding would suggest that the active-site Cys residue in Ag AP-AChE is not targetable, a conclusion advanced in a recent reconsideration of this issue [18] . Further questions regarding Cys-targeting inhibitors arise from our own observation that such inhibitors can inhibit the human AChE ( h AChE) in irreversible fashion, although this enzyme has no Cys residue near its active site [16] .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been reported that iodoacetamide-containing AChE inhibitors do not bond covalently to Ag AP-AChE [17] . Since iodoacetamide is a commonly used sulfhydryl agent, such a finding would suggest that the active-site Cys residue in Ag AP-AChE is not targetable, a conclusion advanced in a recent reconsideration of this issue [18] . Further questions regarding Cys-targeting inhibitors arise from our own observation that such inhibitors can inhibit the human AChE ( h AChE) in irreversible fashion, although this enzyme has no Cys residue near its active site [16] .…”
Section: Introductionmentioning
confidence: 99%
“…This alignment [59] along with site-directed mutagenesis work with lancelet AChE [59] and the previously reported sensitivity of aphid AChEs to sulfhydryl inhibitors [60, 61] collectively led to discussions on whether Cys289 or its equivalent in other aphid AP-AChEs is located in the active site [59] and whether it could be used as a target for developing selective aphidicides [62]. …”
Section: Insect-specific Cysteine In Acetylcholinesterasesmentioning
confidence: 99%
“…A sequence alignment of nine AChE sequences (humans, the Florida lancelet [ Branchiostoma floridae ], the electric ray [ Torpedo californica ], the African malaria mosquito, the northern house mosquito, the greenbug, the cotton aphid, the green peach aphid, and the honeybee) identified a cysteine residue, Cys289 in the greenbug AP-AChE, that is absent in human AChE but conserved in insect and lancelet AChEs [ 59 ]. This alignment [ 59 ] along with site-directed mutagenesis work with lancelet AChE [ 59 ] and the previously reported sensitivity of aphid AChEs to sulfhydryl inhibitors [ 60 , 61 ] collectively led to discussions on whether Cys289 or its equivalent in other aphid AP-AChEs is located in the active site [ 59 ] and whether it could be used as a target for developing selective aphidicides [ 62 ].…”
Section: Insect-specific Cysteine In Acetylcholinesterasesmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that although both Cys residues could be involved in the inactivation, Cys310, near the top of the gorge was more accessible and more easily reduced by the disulfide reagents, resulting in enzyme inactivation. Many aphids, mosquitoes, and other insects have Cys residues homologous to Cys310 (Pezzementi et al, 2006; Pang, 2006a; Pang, 2006b; Rowland et al, 2008), and are sensitive to reduction by sulfhydryl reagents (Zahavi et al, 1972; Smissart, 1976), raising the possibility of this residue as a target for specific insecticides.…”
Section: Introductionmentioning
confidence: 99%